THE PROBLEM OF EQUALENT TRANSLATION OF ONIMS FROM GERMAN INTO RUSSIAN - M. A. Chigasheva (Vestnik MGIMO-Universiteta)
The given paper deals with certain lexical peculiarities of contemporary German sociopolitical discourse which may cause certain difficulties when translating into Russian. The interest in the lexical system is deliberate as this system is the most dynamic level of a language and as it reflects all the changes of the outside world. The main emphasis in it is placed on common nouns and proper names as well as on the lexical units formed as a result of the deonimization process. The distinctive feature of the modern German language is popularity of such lexical tokens as the linguistic expressive means, their clearly expressed negative connotation and the loss of relatedness with concrete people. The study of proper names and common names, created by the former including the comparative aspect may be of practical interest particularly at the lessons of the socio-political translation, as well as from the point of cultural linguistics since such lexical units express the specificity of the cultural background of the German native speaker. The deonimization process has universal character and is common for many European languages. Its study, in the comparative aspect, becomes extraordinary relevant especially today due to the process of globalisation when intercultural contacts gain special importance. Besides, proper names cross the language borders easily, however, if they contain changed meanings, they can cause a misunderstanding and as a result even a distortion. The main purpose of socio-political translation classes in a university is the development of the professional competence as well as the linguistic one. These lexical peculiarities have special importance as in the final analysis they will let graduates accomplish communicative tasks in their professional sphere.